Introduction to crowd science - Still, G. Keith (2014)
"This well-grounded and practical guide highlights the underlying causes of crowd disasters and mass fatalities--living readers insight into the root causes of crowd related accidents. It presents a clearer understanding of crowd dynamics and provides the reader with fundamental modeling techniques to plan and manage and improve crowd safely in places of public assembly. The book is written for students and professionals in a number of areas such as event planning, licensing/approval and event operation, including the emergency services." --
"Preface 'Safety First' is 'Safety Always'. Charles M. Hayes The safety of the people shall be the highest law. Marcus Tullius Cicero In this book, we* demonstrate how crowd accidents and incidents--specifically mass fatalities in crowded spaces--can occur, and how they can be avoided using simple, practical and low-cost analysis techniques. We explore the underlying causes of accidents and incidents, and provide the reader with a comprehensive set of tools for crowd risk analysis and crowd safety engineering. These tools, methods and worked examples come for over two decades of consulting on major crowd projects. We have also been teaching, training and developing applications around the world for over 10 years; these methods have been applied to many major events in the United Kingdom, the United States and elsewhere. We demonstrate real-world case studies from a range of event sites and demonstrate how we ensured safety in some complex sites. Throughout the book we focus on the practical elements of developing the crowd risk analysis and crowd safety aspects of an event plan, with consideration to places of public assembly, major events and large-scale urban environments. We define a range of modelling techniques, including line diagrams that represent crowd flow, calculations of the speed at which a space can fill, and of the time it takes for that space to reach critical and then crush density. We define a method of understanding, * Over the years, a variety of associates have worked with the author, in the field, on operational research, development and teaching activities described throughout the book. Their names are listed in the acknowledgements. Although we are using the academic convention hroughout this book, "we" refers to the author experience and"--
Includes index.
Keywords: Crowds; Crowd control; Collective behavior; TECHNOLOGY & ENGINEERING / Industrial Health & Safety; PSYCHOLOGY / Social Psychology; TRANSPORTATION / Public Transportation